Audience Motivation for Watching the Interactive Talk Show Hallo Permirsa on LPP TVRI Riau Station - Septi Sabariah Dali Munthe; Suyanto Suyanto (South East Asian Management Concern, 2026)
Hallo Pemirsa is a karaoke-type television program that offers direct interaction between the audience and the presenter through interactive services. Hallo Pemirsa is a program of LPP TVRI Station Riau that has the most interactive audience. Audience activity on the program results from choosing to use the media with certain considerations. The research aims to analyze audience motives and factors that encourage audiences to watch the Hallo Pemirsa Program of LPP TVRI Riau Station. The research uses descriptive qualitative methods, drawing on McQuail's concept of media use. The research subjects were 7 informants, selected purposively. The results showed that: (1) the motives of audiences in watching the interactive dialogue program Hallo Pemirsa depart from three motives for media use only, namely, personal identity motives, social integration and interaction motives, and entertainment motives. Informants stated that information motive is not a motive in watching the Hallo Pemirsa program; (2) two factors are found that encourage audiences to watch this program, namely internal factors, including motive factors, attitudes, emotions, habits, and personal experiences, and external factors, including time factors, program content, media personalities, and media